Akibat Hukum dari Keterlambatan Pembayaran Spaylater bagi Pengguna E-Commerce Shopee - Ni Kadek Pingkan Putri Natalia; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
Spaylater is a feature in Shopee's E-Commerce that is used as a payment method that provides loan funds for its users to make transactions on Shopee's E-Commerce. In using the spaylater feature, terms and conditions must be met. However, users often ignore these terms and conditions, resulting in legal consequences. Based on this phenomenon, this study reviews the legal arrangements regarding spammers in Shopee's E-Commerce and reveals the legal consequences that arise if Shopee's E-Commerce users delay in paying the spamer. The type of research used in this research is normative legal research through statutory and conceptual approaches, the data used are primary and secondary legal materials obtained through library research techniques. Furthermore, the data that has been collected is processed and analyzed descriptively qualitatively. The results of the study indicate that the legal arrangement that regulates the spaylater in Shopee's E-Commerce is the Agreement as regulated in Article 1313 of the Civil Code. The legal consequences that arise if a Shopee E-Commerce user delays the payment, namely the user's Shopee account will be frozen by Shopee, the user will receive consequences in the form of field billing and the user's personal data is then recorded in the financial information service system which can prevent users from getting financing from Banks and other companies.